2011
DOI: 10.3233/efi-2010-0890
|View full text |Cite
|
Sign up to set email alerts
|

The changing educational needs of subject librarians: A survey of UK practitioner opinions and course content

Abstract: The fitness for purpose of professional education for library work has been constantly debated. Librarianship education and library practice have changed significantly as a result of technological, social and other factors affecting information provision and use. The key role of subject librarian in academic libraries has been particularly affected by both technological and pedagogical developments that have transformed the information arena, expanded their teaching activities and raised questions about the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
(79 reference statements)
1
15
0
1
Order By: Relevance
“…This is an alternative view to that of "managing and providing access to information" (D, 011), held by the same participant, indicating there are two almost opposing viewpoints of librarianship which may be held by this community of interest -the gatekeeper-enabler viewpoints. This example indicates that this shift may not have completely taken place and supports the work of Simmons and Corrall (2011) and Oyelude and Bamigbola (2012) who suggest libraries may now be viewed increasingly as gateways as well as gatekeepers.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This is an alternative view to that of "managing and providing access to information" (D, 011), held by the same participant, indicating there are two almost opposing viewpoints of librarianship which may be held by this community of interest -the gatekeeper-enabler viewpoints. This example indicates that this shift may not have completely taken place and supports the work of Simmons and Corrall (2011) and Oyelude and Bamigbola (2012) who suggest libraries may now be viewed increasingly as gateways as well as gatekeepers.…”
Section: Discussionsupporting
confidence: 52%
“…They will therefore act as IL "producers" to help others to develop their own information literacies. Since the days of bibliographic instruction and user education, research into LIS programmes (Shonrock and Mulder 1993;Albrecht and Baron 2002;Ishimura and Bartlett 2009;Gerolimos 2009;Simmons and Corrall 2011) has considered the issues and practicalities of developing LIS graduates skill-sets in the curriculum, and there are many examples of courses and modules devoted to the delivery of bibliographic instruction, user education, and IL in LIS through recent history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UK library and information students on CILIP-accredited courses are required to learn about teaching and training skills, which form part of CILIP's Professional Knowledge and Skills Base (CILIP 2013). There is also demand from employers and library and information science (LIS) professionals for new graduates to have teaching skills and for them to have learned these during the postgraduate course (Simmons and Corrall 2011), but in 2010 just three UK library courses offered optional teaching-related modules (Simmons 2010). Bewick and Corrall (2010) found that 15 out of 78 surveyed librarians had gained a formal teaching-related qualification, although only one librarian reported a postgraduate diploma in librarianship as the source of their teaching skills.…”
Section: How Librarians Develop Teaching Competencementioning
confidence: 99%
“…In 2009 an analysis of the courses required in ALA accredited programs in the US shows that the typical core curriculum includes now research and information technology, in addition to the traditional librarianship subjects [10]. A 2010 study investigating the content of postgraduate librarianship courses in the UK reveals that 'research methods and information retrieval, appear in almost all courses as core units or as a significant part of a core unit' and 80% of the subject librarians participating in the study considered research skills/methods as the third core competency required in the profession, after information literacy and information retrieval skills [21]. With both the US and the UK markets for LIS education programs offering research courses as core curriculum subjects, it becomes imperative for the Australian LIS education to offer similar courses in order to be competitive on the international market.…”
Section: The Importance Of Fundamental Research For Information Educamentioning
confidence: 98%